Dirofilaria immitis and Angiostrongylus vasorum : epidemiology and impact of major heartworms in carnivores in Portugal - Alho, Ana Margarida Pignateli Vasconcelos de Assunção (2018)
Tese de Doutoramento em Ciências Veterinárias, Especialidade de Sanidade Animal